2017
DOI: 10.1111/joms.12323
|View full text |Cite
|
Sign up to set email alerts
|

The Legitimacy of Inequality: Integrating the Perspectives of System Justification and Social Judgment

Abstract: To explain the legitimation of inequality among the members of a social system, we blend system justification theory and the theory of social judgment. We identify adaptation and replacement as two major mechanisms of inequality legitimation and examine their influence in the unique setting of a natural experiment, the reunification of socialist East Germany and capitalist West Germany. We show that the new members of a society in which inequality is broadly endorsed and perceived as enduring will adapt to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 106 publications
(155 reference statements)
0
64
0
1
Order By: Relevance
“…Three of our contributors help us to understand how, once established, the ideology of institutionalized inequality is sustained through talk. Analysing data from the German General Social Survey, Haack and Sieweke () demonstrate how, after the reintegration of East and West Germany, East Germans very quickly ‘normalized’ the high degree of income inequality in their new capitalist society. Two critical variables determined the pace of legitimation of inequality – the time an individual spent under the old regime of assumed equality and the pace at which new members are born into the new regime of capitalist inequality.…”
Section: How Talk Maintains Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Three of our contributors help us to understand how, once established, the ideology of institutionalized inequality is sustained through talk. Analysing data from the German General Social Survey, Haack and Sieweke () demonstrate how, after the reintegration of East and West Germany, East Germans very quickly ‘normalized’ the high degree of income inequality in their new capitalist society. Two critical variables determined the pace of legitimation of inequality – the time an individual spent under the old regime of assumed equality and the pace at which new members are born into the new regime of capitalist inequality.…”
Section: How Talk Maintains Inequalitymentioning
confidence: 99%
“…Two critical variables determined the pace of legitimation of inequality – the time an individual spent under the old regime of assumed equality and the pace at which new members are born into the new regime of capitalist inequality. The two measures, Haack and Sieweke () conclude, serve as proxies for the collective legitimation of inequality. Through socialization (i.e., talk of what is acceptable, normal and valued in a society), we gradually begin to see inequality as a natural and maybe even a desirable state of the human condition.…”
Section: How Talk Maintains Inequalitymentioning
confidence: 99%
“…Also, research may explore micro-level mechanisms that are involved in the process of institutionalization. For instance, research has shown that two micro-level mechanisms explain institutional change over time (Haack and Sieweke 2017;Tilcsik 2010): First, the members of the organization may change their attitudes towards e-participation. That is, the longer members deal with e-participation, the more positive their attitude towards e-participation, which contributes to the institutionalization of e-participation in public administrations.…”
Section: Discussion and Implications: Towards A Research Agendamentioning
confidence: 99%
“…The inequalities of wealth and income do not fully capture the inequalities that affect an individual's socioeconomic life (Bapuji & Mishra, 2015). Echoing this argument, some scholars have defined inequality as "the uneven distribution of economic resources, such as income and wealth, as well as, of other social resources, such as information and social integration, which contribute to income or wealth as intervening variables" (Haack & Sieweke, 2018:2).…”
Section: Economic Inequality and The Caste Systemmentioning
confidence: 99%
“…In addition to paying limited attention to the role of institutions in inequality, previous research has also paid less attention to theorizing the construct of economic inequality. Although extant definitions of economic inequality allude to uneven dispersion in resource possession and access (Bapuji, 2015;Haack & Sieweke, 2018;Mair, Wolf & Seelos, 2016), these definitions have rarely been contextualized, and the relationship between the elements of possession and access has not been theorized. Further, scholars often use economic inequality interchangeably with income inequality and wealth inequality, thus pointing to the need to clarify and elaborate what economic inequality is.…”
mentioning
confidence: 99%